(untitled) (Fiep Bulletin - online, 2015)
Introduction: The obesity is being considered a world epidemic, reaching all the age groups and a lot of populations, showing discharges correlations with many risk factors, besides in the pediatric population. It is necessary to evaluate the corporal composition, to verify the percentile of fat it is in healthy considerable levels. According to HEYWARD et al. 2001, the method antropométrico, now is the field method more used to determine the percentile of fat, due to application easiness in great populations, low cost of the equipments and invasive little. Objective: To compare the results of two methods of measures of the percentile of fat in children. Methods: The sample was constituted by 21 children from 10 to 12 years, with age (11,05 ± 0,38), stature (146,02 ± 8,04) and corporal mass (37,09 ± 8,08). The corporal fat was measured through two methods, and one of them using two protocols of the method SLAUGTHER (1988): PROT. 1 - it uses the folds triceps and subscapular (%GC = 0,783 x (doc) + 1,6) and PROT. 2 - triceps and calf (%GC = 0,735 x (doc) + 1,0). The second method was the dual-energy X-ray absorptiometry (DXA), using apparel of the Lunar mark, I model DPX-IQ, software " 4.6A. They were followed all the recommendations of the manufacturer and all the children had a free and illustrious form signed by the parents. Results: The results found by the two methods they were: %GDXA (15,87 ± 5,76); %Gprot.1 (19,06 ± 4,74) and %Gprot.2 (20,50 ± 6,59).Discussion: It is observed that the medium values of %Gprot.1 and of %Gprot.2 they differ significantly of the medium values of %GDXA, however. %Gprot.1 and %Gprot.2 presented strong correlation with %GDXA, 0,91 and 0,90, respectively, being both correlations significant. It is still the protocols of corporal composition, they were validated in other pediatric populations. This way becomes more necessary studies for better clarifications.